Global monitoring report 2004 : policies and actions for achieving the Millenium Development Goals and related outcomes.. (International Bank for Reconstruction and Development, the World Bank, 2004)
An integrated assessment of the policies and actions by developing countries, developed countries, and international financial institutions that are needed to achieve the Millennium Development Goals. The Report provides an assessment of how the various parties are playing their part and highlights progress on the development policy agenda.